Study the Effect of Cutting Parameters on Temperature Distribution and Tool Life During Turning Stainless Steel 316L - Akbar, Ahmed A.; Shwaish, Raed R.; Hadi, Naba D. (Al-Khwarizmi Engineering Journal, 2018)
This paper is focused on studying the effect of cutting parameters (spindle speed, feed and depth of cut) on the response (temperature and tool life) during turning process. The inserts used in this study are carbide inserts coated with TiAlN (Titanum, Aluminium and Nitride) for machining a shaft of stainless steel 316L. Finite difference method was used to find the temperature distribution. The experimental results were done using infrared camera while the simulation process was performed using Matlab software package. The results showed that the  maximum difference between the experimental and simulation results was equal to 19.3 , so, a good agreement between the experimental and simulation results  was achieved. Tool life was decreased when spindle speed and feed were increased.